INVESTIGATING THE GOVERNMENT REVENUE–EXPENDITURE NEXUS: EMPIRICAL EVIDENCE FOR THE FREE STATE PROVINCE IN A MULTIVARIATE MODEL - OMOSHORO-JONES, Oyeyinka S. (Theoretical and Practical Research in Economic Fields; Vol 11 No 2 (2020): TPREF, Volume XI, Issue 2(22), Winter 2020DO - 10.14505/tpref.v11.2(22).08, 2020)
This paper examines the government revenue–expenditure nexus for the Free State Province in a multivariate vector error correction model (VECM) using real GDP and inflation as control variables over the period 2004Q2–2018Q1.Cointegration and intertemporal (causal) links among variables were established employing Johansen (1995) and Toda-Yamamoto (1995) non-Granger causality tests. The results of the cointegration analysis confirm the existence of a long-run relationship between variables. The results of the causal analyses show a bidirectional causality between government revenues and expenditures in both the long-run and short-run supporting the fiscal synchronization hypothesis. Real GDP and inflation individually Granger-causes government revenue, in both the long-run and short-run, stressing their importance on generating revenue. Based on these findings, an isolated fiscal measure to raise tax-revenues or cut expenditure will exacerbate fiscal imbalance. On the policy front, the Free State government should adhere to a planned budget process, devise innovative revenue-generating strategies to circumvent the burden of producing inflation revenue, as well as utilize its autonomy on fiscal instruments to maintain a sustainable fiscal policy path, and stimulate economic growth.